2020
DOI: 10.7554/elife.58147
|View full text |Cite
|
Sign up to set email alerts
|

An adjunctive therapy administered with an antibiotic prevents enrichment of antibiotic-resistant clones of a colonizing opportunistic pathogen

Abstract: A key challenge in antibiotic stewardship is figuring out how to use antibiotics therapeutically without promoting the evolution of antibiotic resistance. Here, we demonstrate proof of concept for an adjunctive therapy that allows intravenous antibiotic treatment without driving the evolution and onward transmission of resistance. We repurposed the FDA-approved bile acid sequestrant cholestyramine, which we show binds the antibiotic daptomycin, as an ‘anti-antibiotic’ to disable systemically-administered dapto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 43 publications
(44 reference statements)
4
31
0
Order By: Relevance
“…Here, we have shown that cholestyramine can prevent enrichment of resistance following the de novo emergence of daptomycin-resistance in E. faecium populations colonizing the intestines (Experiment 1, Fig 1). Previously, we had shown that cholestyramine could prevent the enrichment of preexisting resistant clones [1] (a result we saw again in Experiment 2; Figure 3). These results further show the promise of cholestyramine treatment for preventing off-target resistance evolution emerging via multiple genetic pathways during daptomycin treatment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Here, we have shown that cholestyramine can prevent enrichment of resistance following the de novo emergence of daptomycin-resistance in E. faecium populations colonizing the intestines (Experiment 1, Fig 1). Previously, we had shown that cholestyramine could prevent the enrichment of preexisting resistant clones [1] (a result we saw again in Experiment 2; Figure 3). These results further show the promise of cholestyramine treatment for preventing off-target resistance evolution emerging via multiple genetic pathways during daptomycin treatment.…”
Section: Discussionsupporting
confidence: 72%
“…In the experiment testing the timing of cholestyramine administration, we also used the daptomycin-resistant strain BL00239-1-R (MIC c = 8.6). This resistant strain was isolated from a mouse colonized with BL00239-1 after experimental daptomycin treatment, as previously described [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile acid sequestrant cholestyramine binds daptomycin. In mice, cholestyramine reduced faecal shedding of daptomycin‐resistant E. faecium up to 80‐fold 15 …”
Section: And Matchmentioning
confidence: 99%
“…How does resistance evolve in multiple drug treatment scenarios (McLeod and Gandon, 2021), and what are the interaction effects with co-occurring pathogens? What are the best practices for treating patients, given this knowledge (Morley et al, 2020)? What features of newly designed drugs are optimal in the face of these evolutionary processes?…”
Section: George H Perrymentioning
confidence: 99%